Deciphering Prognostic Value of TTN and Its Correlation With Immune Infiltration in Lung Adenocarcinoma - Chen, Jianing; Wen, Yaokai; Su, Hang; Yu, Xin; Hong, Ruisheng; Chen, Chang; Su, Chunxia (Frontiers in Oncology, 2022)
Background: Lung adenocarcinoma (LUAD) is the most common type of lung cancer, accounting for around 40%. Despite achievements in the treatment approach, the prognosis is still dismal, with overall survival of fewer than five years. Thus, novel prognostic biomarkers are needed to predict the clinical outcomes of individual patients better. TTN has a high mutation rate in the LUAD, which encodes a large abundant protein of striated muscle. However, the value of TTN in prognosis and the immune environment are poorly understood. Methods: We investigated the clinicopathological characteristics, transcriptional and protein level, prognostic value, biological function, and its relationship with immune infiltration of TTN gene in LUAD patients through bioinformatics analysis. Results: TTN expression was significantly lower in LUAD than that in normal lung tissue. Lower TTN expression was associated with worse survival. Besides, TTN highly expressed in alveolar type 2 cells which were surmised as the origin of LUAD. Conclusion: Our findings indicated the potential prognostic value of TTN and its role as a biomarker for determining the immune infiltration levels in patients with LUAD.